A new bacterial-derived biosurfactant for biotechnological applications in the oil industry: production, optimization, biosurfactant functional and physicochemical characterization. Issue 4 (20th March 2023) - Elghoul, Marwa; Bouassida, Mouna; Ghribi, Dhouha; Mnif, Inès
Abstract: Aiming the potential application of lipopeptide biosurfactant (BioS) in bioremediation, we studied its production by a novel, isolated strain of Bacillus sp. MI27. Using the experimental design methodology, a novel medium composed of 2% sucrose, 0.27% Na2HPO4, 0.2% ammonium sulfate, 0.02% NaCl, 0.02% CaCl2, 0.02% MgSO4, 0.001% MnSO4, 0.06% KH2 PO4, 0.005% FeSO4 and 0.005% ZnSO4 was optimized. With this composition, strain MI27 produces 1.4 g/L BioS with maximum surface tension (ST) reduction of 23 mN/m and a dispersion diameter of around 10 cm. Emulsifying and foaming activities have been also confirmed. The critical micelle concentration (CMC) value was about 120 mg/L with corresponding ST of 23 mN/m. The dispersion and emulsification index (EI) were about 12 cm and 45% at 1, 000 mg/L respectively. Moreover, the foaming capacity, stable over 1 h of incubation, was about 80% at 1, 000 mg/L. Additionally, we studied the effect of different pH, temperature and salinities on MI27 BioS activity and stability. Obtained results showed interesting surface activities at extreme physicochemical conditions, especially at acidic and alkaline pH values, high and low temperatures and higher salinities. All these characteristics enable the possible application of BioS in water treatment biotechnology under diverse environmental conditions. HIGHLIGHTS: Experimental methodology to optimize lipopeptide production by Bacillus sp. MI27. Optimized medium composed only of sucrose, ammonium sulfate and mineral elements. The lipopeptide had a CMC value of 120 mg/L with a surface tension of 23 mN/m. It disperses and emulsifies oil to about 12 cm and 45% with a foaming capacity of about 80%. The lipopeptide showed surface activity and stability at extreme physicochemical conditions.